La Repubblica : dieci anni / La Repubblica
Todos los ejemplares son suplementos de números del aǫ 1986 | Contiene: Vol. I: 1976 -- Vol. II: 1977 -- Vol. III: 1978 -- Vol. IV: 1979 -- Vol. V: 1980 -- Vol. VI: 1981 -- Vol. VII: 1982 -- Vol. VIII: 1983 -- Vol. IX: 1984 -- Vol. X: 1985